Factors in the Growth of Vtuber Livestreaming Entertainment Phenomenon in Japanese Society - Otto Nauma Tambunan; Andy Bangkit Setiawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This research analyses the driving factor for the development of Vtuber livestreaming entertainment in Japanese society, that happen during the last COVID 19 pandemic. Vtuber is a live streaming entertainment where a streamer use 2D avatar that they fill their voice in so that the character are the one doing the livestream. The purpose of this study is to find out what is the factor that led to the rapid Growth of Vtuber in the world of live streaming entertainment in japan. This reseach uses Qualitative reseach thematic method analytical approach with open discussion data on Quora.Jp by selecting discussion topics that related to Vtuber in it. The conclusion of this research is can develop in Livestreaming entertainment due to the help of several factor, such as Vtuber relationship with Fans, Vtuber, Agency, and How they present their Vtuber character